A highly magnified candidate for a young galaxy seen when the universe was 500 Myrs old - Wei, Zheng; Zitrin, Adi; Carrasco, Mauricio; Bartelmann, Matthias (Arxiv, 2012)
The early Universe at redshift z\sim6-11 marks the reionization of the intergalactic medium, following the formation of the first generation of stars. However, those young galaxies at a cosmic age of \lesssim 500 million years (Myr, at z \gtrsim 10) remain largely unexplored as they are at or beyond the sensitivity limits of current large telescopes. Gravitational lensing by galaxy clusters enables the detection of high-redshift galaxies that are fainter than what otherwise could be found in the deepest images of the sky. We report the discovery of an object found in the multi-band observations of the cluster MACS1149+22 that has a high probability of being a gravitationally magnified object from the early universe. The object is firmly detected (12 sigma) in the two reddest bands of HST/WFC3, and not detected below 1.2 μm, matching the characteristics of z\sim9 objects. We derive a robust photometric redshift of z = 9.6 ± 0.2, corresponding to a cosmic age of 490 ± 15Myr (i.e., 3.6% of the age of the Universe). The large number of bands used to derive the redshift estimate make it one of the most accurate estimates ever obtained for such a distant object. The significant magnification by cluster lensing (a factor of \sim15) allows us to analyze the object's ultra-violet and optical luminosity in its rest-frame, thus enabling us to constrain on its stellar mass, star-formation rate and age. If the galaxy is indeed at such a large redshift, then its age is less than 200 Myr (at the 95% confidence level), implying a formation redshift of zf \lesssim 14. The object is the first z>9 candidate that is bright enough for detailed spectroscopic studies with JWST, demonstrating the unique potential of galaxy cluster fields for finding highly magnified, intrinsically faint galaxies at the highest redshifts.